Advances in intestinal epithelium and gut microbiota interaction - Yang, Sen; Liu, Hanmin; Liu, Yang (Frontiers in Microbiology, 2025)
The intestinal epithelium represents a critical interface between the host and external environment, serving as the second largest surface area in the human body after the lungs. This dynamic barrier is sustained by specialized epithelial cell types and their complex interactions with the gut microbiota. This review comprehensively examines the recent advances in understanding the bidirectional communication between intestinal epithelial cells and the microbiome. We briefly highlight the role of various intestinal epithelial cell types, such as Paneth cells, goblet cells, and enteroendocrine cells, in maintaining intestinal homeostasis and barrier function. Gut microbiota-derived metabolites, particularly short-chain fatty acids and bile acids, influence epithelial cell function and intestinal barrier integrity. Additionally, we highlight emerging evidence of the sophisticated cooperation between different epithelial cell types, with special emphasis on the interaction between tuft cells and Paneth cells in maintaining microbial balance. Understanding these complex interactions has important implications for developing targeted therapeutic strategies for various gastrointestinal disorders, including inflammatory bowel disease, metabolic disorders, and colorectal cancer.